Analysis of Artificial Intelligence (AI) Utilization for Improving Motor Skills Learning Outcomes among Elementary School Teacher Education (PGSD) Students - Khaerul Anam; Muhamad Sadli; Hadi Wijaya (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This study explores the use of artificial intelligence (AI) to improve motor skills learning outcomes for elementary school teacher education (PGSD) students. The research investigates how AI can provide timely feedback and personalized instruction in teaching motor skills. Data analysis methods include surveys, observations, and evaluations of learning outcomes. The research findings reveal the following: 1) Female students' motor skills are classified as moderate, with an average score of 200. The classification criteria for female students' motor skills are excellent (5.67%), good (24.33%), moderate (30.33%), poor (32.67%), and very poor (3%). 2) Male students' motor skills are also categorized as moderate, with an average score of 200. The percentage breakdown for male students' motor skills is as follows: excellent (7.32%), good (25.61%), moderate (37.80%), poor (29.39%), and very poor (4.88%). The results indicate that integrating AI into motor skills learning significantly enhances the academic performance of PGSD students. These findings highlight the importance of incorporating AI technology in teacher education, particularly to enhance the motor skills development of PGSD students. The research supports the concept that AI can effectively support motor skills learning at this educational level.